Relational Egalitarianism, Paternalism, Adults and Children: A Puzzle - Andreas Bengtson (Ergo, An Open Access Journal of Philosophy)
Relational egalitarianism is a theory of justice according to which people must relate as equals. However, not just any inegalitarian relation is unjust, i.e., the fact that parents do not relate as equals to their children is not unjust. Whereas an adult treating another adult paternalistically is objectionable from the point of view of relational egalitarianism, parent-child paternalism is not. What may explain this difference in judgment? I refer to this as the Puzzle. I discuss four justifications of the Puzzle and argue that none of them is satisfactory. In the final part of the paper, I discuss where this leaves relational egalitarianism as a theory of justice.